Analytical and Experimental Verification of Interleaved Trapezoidal Heat Sink - Chen, Hong-Long; Wang, Chi-Chuan (My University, 2017)
The objective of this paper is to explore the technique for lowering the contraction and hydraulic developing region pressure drop, in order to gain more airflow for electronic cooling heat sink for the same footprint and fin number. By combining two different geometrical perimeter shapes of fins, odd number is rectangular shape, and even number is trapezoidal shape, this new fin module design gains extra 10% airflow with little loss or equivalent thermal performance. Current data center server is suffering from too little airflow to cool essential chips due to enormous flow impedance for packing too many components inside. This technology is the solution to resolve this bottleneck. The precious extra 10% more airflow not only cools CPU chip itself; but also quite beneficial to cool other heating components inside servers. Also, this new design excels in low velocity of 2 m/s for thermal performance compared to original design. Lower velocity is equal to lower RPM of fan that leads to the advantage of energy saving.
Keywords: Heat sink; pressure drop; friction factor; electronic cooling